Alzheimer's Disease–Related Dementias Summit 2016: National research priorities. (5th December 2017) - Corriveau, Roderick A.; Koroshetz, Walter J.; Gladman, Jordan T.; Jeon, Sophia; Babcock, Debra; Bennett, David A.; Carmichael, S. Thomas; Dickinson, Susan L.-J.; Dickson, Dennis W.; Emr, Marian; Fillit, Howard; Greenberg, Steven M.; et al.
Abstract : Goal 1 of the National Plan to Address Alzheimer's Disease is to prevent and effectively treat Alzheimer disease and Alzheimer disease–related dementias by 2025. To help inform the research agenda toward achieving this goal, the NIH hosts periodic summits that set and refine relevant research priorities for the subsequent 5 to 10 years. This proceedings article summarizes the 2016 Alzheimer's Disease–Related Dementias Summit, including discussion of scientific progress, challenges, and opportunities in major areas of dementia research, including mixed-etiology dementias, Lewy body dementia, frontotemporal degeneration, vascular contributions to cognitive impairment and dementia, dementia disparities, and dementia nomenclature.